(3QLGd GHf OGhO GdMdjs - (3GdMdj, GHf OGhO, CHh eMeO, Jbj GdOjf, GdMSf Hf Ydj Hf OGhO, (B740 (3g`s
(3ChdgG (B:s
(3jG ejSQ dcd YSjQ(B... (3hHYO aEfj deG fXQJ aj CUhd GdaJGhi GdabgjI (B...s
(3BNQgG (B:s
(3CHh gGQhf Gdecaha(B... (3CHh jYbhH GdeYQj(B... (3Je GdcJGHs
(3JHUQI GdYfhGf (B:s
(3QLGd GHf OGhO GdMdjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B204s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B568s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B568s
Keywords: (3GdJGQjNs